Proximate analysis and vitamin B contents of fresh-made, canned chickpea and broad bean dips commercially produced in Jordan. - Seham M Abu Jadayil; Ali K Alsaed; Iman F Mahmoud; Leena M Ahmad; Fatena Afaneh; Hanaa Khalaf; Mohammed Z Soudi (PLoS ONE)
Background Chickpea and broad bean dips are among the most popular legume-based dishes in the Middle Eastern countries. They are either made freshly by restaurants or sold in cans. Various manufacturing processes may enhance or reduce the chemical compositions of any food products, including these dips, which in turn can affect their nutritional values and health benefits. Therefore, this study aimed to evaluate the nutritional values of the chickpea and broad bean dips and examine the possible differences between those made freshly and those sold as canned products. Methods Fresh-made and canned chickpea and broad bean dips were obtained from various restaurants and factories in Jordan and were analyzed for their proximate analysis, titratable acidity, and pH value. Furthermore, vitamins B were analyzed using liquid chromatography-mass spectrometry. Results Significant differences were detected between fresh-made and canned chickpea dips, with the former containing higher quantities of fiber (10.96g ± 0.32) while the latter containing higher quantities of proteins (8.06g ± 0.29), fats (8.05g ± 1.08), and the vitamins B1 (0.46 ± 0.02) and B5 (0.87 ± 0.02). On the other hand, a significant difference was detected between fresh-made and canned broad bean dips, while the latter contained higher quantities of carbohydrates (20.94g ± 0.78) and tested B-vitamins (except for B6). These detected differences may be due to different variances of chickpeas and broad beans used, preparation methods, and/or the addition of other ingredients. Conclusion Our results indicate that both chickpea and broad bean dips prepared/sold in Jordan were of high nutrition values in terms of proximate analysis, and vitamins B, with higher quantities observed in the canned dips. Higher titratable acidity and lower pH were also significantly found in the canned dips. This study adds to the existing literature regarding the fresh-made and canned chickpea and broad beans dips produced and sold in Jordan. Moreover, this study shows that canned chickpea and broad beans dips can provide consumers with comparable nutrient values to those provided by the freshly made dips. Nevertheless, these findings warrant more investigations.